MULTIPLEX ANALYSIS OF PERIPHERAL BIOMARKERS IN SCHIZOPHRENIC PATIENTS WITH LONG-TERM ANTIPSYCHOTIC THERAPY - A. S. Boiko; I. S. Losenkov; E. G. Dmitrieva (Разработка и регистрация лекарственных средств)
Complex clinical and biological study of 115 schizophrenic patients with long-term antipsychotic treatment was carried out. Concentrations of brain-derived neurotrophic factor (BDNF) and prolactin levels in blood serum in schizophrenic patients and healthy subjects were determined to multiplex analyzer MAGPIX (Luminex, USA) using the kits MILLIPLEX® MAP (Merck, Germany). BDNF concentration was significantly correlated with the severity of positive symptoms in schizophrenic patients. Antipsychotics induced hyperprolactinemia is the need to monitor the level of prolactin to develop personalized approaches to treatment and improve the quality of life of patients.